Exhaled breath condensate pH decreases during exercise‐induced bronchoconstriction. Issue 4 (25th February 2014) - Bikov, Andras; Galffy, Gabriella; Tamasi, Lilla; Bartusek, Dora; Antus, Balazs; Losonczy, Gyorgy; Horvath, Ildiko
Abstract Background and objective Exercise‐induced bronchoconstriction (EIB) is the temporary narrowing of the airways caused by physical exercise. Its exact pathophysiology is unclear; however, acute changes in airways pH may play a role. Exhaled breath condensate (EBC) pH was suggested as a surrogate indicator for airway acid–base status, but its value is also affected by volatile molecules and respiratory droplet dilution. The aim of the study was to assess changes in EBC pH during EIB. Methods Twenty‐two asthmatics who reported breathlessness following exercise and 16 healthy individuals participated in the study. Lung function test was performed and exhaled breath samples were collected for pH, dilution factor and volatile compound pattern measurements (Cyranose 320) pre‐exercise and at 0, 10, 20 and 30 min after physical exercise challenge. Fractional exhaled nitric oxide was measured before exercise. Results EIB developed in 13 asthmatic subjects. In these participants, but not in the EIB‐negative asthmatics (P = 0.51), EBC pH reduced significantly during exercise (P = 0.01). In addition, changes in EBC pH were related to the degree of bronchospasm in the EIB‐positive group (P = 0.01, r = 0.68). Exhaled volatile pattern became altered (P < 0.05) during exercise in all subjects (asthmatics and controls). EBC pH changes were not related to EBC dilution or volatile compound pattern alterations (P > 0.05). Conclusions The development of EIB was related to acute changes of EBC pH, which suggest the role of airway pH decrease in the pathophysiology of EIB. Exercise‐induced changes in exhaled biomarkers suggest methodological precautions to avoid physical exercise before performing exhaled breath tests.